Community Design Solutions, 2018-2020 - (:unkn) unknown (My University, 2020)
Community Design Solutions (CDS) is a funded design center in SARUP that assists non-profit agencies, civic groups, communities, and campuses throughout Wisconsin. CDS provides preliminary design and planning services to undeserved communities and agencies. Students from SARUP work with Director, Carolyn Esswein, clients, and faculty to develop concepts that promote positive change, stimulate funding opportunities, and serve as a catalyst for continued investment.